UMA ANÁLISE SOBRE A EQUIPE MULTIDISCIPLINAR – NUGED E O PAPEL DO PSICÓLOGO ANTE AS AÇÕES DE PERMANÊNCIA E ÊXITO NO IFMS. - Elizandra Prates de Oliveira Miranda (2022)
The present study aims to reflect on the performance of the psychology professional at the Instituto Federal de Mato Grosso do Sul, in particular, through the high rates of evasion and retention. In this sense, it proposes to analyze the Strategic Plan of Permanence and Success of the Instituto Federal de Mato Grosso do Sul, with emphasis on the performance as a psychology professional on the campus of the Instituto Federal of the municipality of Jardim. The actions proposed to promote the students' permanence and success, as well as the expectations given to the psychologist, apparently, are aligned with what neoliberalism proposes, bringing in their statements conceptions aimed at an individualizing and stigmatizing proposal. We used as a method the documental research involving bibliographic review and analysis of secondary data having as source the data provided by the Nilo Peçanha Platform. Based on Michel Foucault's theoretical contribution, the analyzes were carried out observing whether they effectively met what they aimed at in their statements and, which statements and which practices were exercised to reach the current context. The results indicate that the actions and actions planned by the psychologist in the plan do not go against the effective overcoming of the reality of evasion and retention, as provided in the statements. Keywords: Permanence and Success. Psychologist's role. Instituto Federal.